متطلبات تطبيق منهجية سيجما ستة Six Sigma لتحسين أداء الجهاز الإدارى بكلية التربية بحفر الباطن جامعة الدمام - عبدالعزيز، عبدالعاطي حلقان أحمد (جامعة سوهاج - كلية التربية, 2014)
هدفت الدراسة إلى محاولة الكشف عن أهم متطلبات تطبيق منهجية سيجما ستة لتحسين أداء الجهاز الإداري بكلية التربية بحفر الباطن – جامعة الدمام، وقد استخدم الباحث في دراسته المنهج الوصفي، مستعيناً باستبانة تم تطبيقها على عينة عشوائية من القيادات الأكاديمية وأعضاء هيئة التدريس بكلية التربية بحفر الباطن – جامعة الدمام.\\\\ وتوصلت الدراسة إلى أن أهم تلك المتطلبات ما يلي: متطلبات مرحلة التعريف: نشر ثقافة منهجية سيجما ستة وأهدافها داخل الكلية، التعرف على احتياجات المجتمع ومؤسساته المختلفة من الكلية، توعية كافة العاملين والجهاز الإداري بالكلية بالأنشطة والعمليات الإدارية التي يمكن تطبيق منهجية سيجما ستة عليها، تدريب العاملين بالكلية على إنجاز المهام بشكل صحيح من المرة الأولى لتجنب احتمال حدوث الأخطاء، متطلبات مرحلة القياس، توفير أساليب متقدمة وتقنيات حديثة لجمع المعلومات والبيانات المطلوبة للتغلب على المشكلات التي تعترض العمليات، تعريف العاملين بالكلية بالأدوات الإحصائية المستخدمة في منهجية سيجما ستة، وكيفية استخدامها، تصميم أدوات قياس العمليات والأنشطة في إطار الوقت المسموح به، إشراك فرق العمل وكافة المنفذين في تصميم أدوات القياس، متطلبات مرحلة التحليل: تشخيص ودراسة أعراض الانحرافات، وتحليل أسبابها، تقييم الأداء والعمل على علاج أوجه القصور، تكوين فرق العمل وتحديد أدوات القياس الملائمة، التعرف على الوضع الحالي للعمليات والأنشطة المختلفة من أجل التأكيد على أسباب زيادة فعالية العملية، متطلبات مرحلة التحسين: تحسين الأجواء وتوفير مناخ تنظيمي ملائم لتحسين أداء الجهاز الإداري بالكلية، وضع مجموعة من الخطط التنفيذية لتحسين العمليات، وضع آليات لعملية مراجعة الأخطاء التي تم الكشف عنها في العمليات أو الأنشطة، اقتراح حلول مبتكرة لعلاج المشكلات المكتشفة، متطلبات مرحلة الضبط: التأكد من سير العمل وفقاً لآليات تنفيذ منهجية سيجما ستة، وضع ضوابط لضمان عدم تدهور الأداء بعد تحسينه، إيجاد آلية دائمة لرصد الأخطاء التي قد تظهر بالعملية وتصحيحها في الوقت المناسب، تحسين نتائج ما بعد التنفيذ في ضوء المعايير الموضوعة سابقاً.\\\\ كما توصلت الدراسة إلى عدم وجود فروق ذات دلالة إحصائية بين متوسط درجات أفراد عينة الدراسة وفقاً لمتغيرات: (الوظيفة الحالية – الدرجة العلمية – عدد سنوات الخبرة) حول المتطلبات الخاصة بالمراحل الآتية لتطبيق منهجية سيجما ستة: (التعريف – القياس – التحليل – التحسين – الضبط). This study aimed to attempt to detect the most important requirements for the application of the Six Sigma methodology to improve the performance of the administrative apparatus at Hafr Ai-batin Faculty of Education - University of Dammam, the the researcher used descriptive method using a questionnaire have been applied to a random sample of faculty members of Hafr Al-batin Faculty of Education - University of Dammam.\\\\ The study found that the most important of these requirements include: requirements of Definition stage: spreading the culture of Six Sigma methodology and objectives within the faculty, meet the needs of the community and its institutions from faculty, educate all employees and the administrative persons with activities and administrative processes that can be applied methodology Six Sigma, training college staff and all employees to accomplish the tasks correctly from the first time to avoid errors . Requirements of measurement stage: Availability of advanced methods and modern techniques to gather information and data needed to overcome the problems encountered in operations, Educate workers with statistic tools used in the methodology of Six Sigma, and how it is used, design tools to measure of processes and activities within the time allowed, involvement of teams and all implementing in the design of measurement tools. Requirements of analysis stage: diagnosis and study of the symptoms of deviations, and analysis of its causes, performance evaluate the work to remedy deficiencies, formation of work teams and determine the appropriate measurement tools, identify the current status of the various processes and activities in order to emphasize the reasons for increasing the effectiveness of the process. Requirements of Improvement stage: provide a regulatory environment conducive to improving the performance of the administrative system, a set of operational plans to improve operations, develop mechanisms for the review of errors that have been detected in the operations or activities, propose innovative solutions to fix the problems discovered. Requirements of Control stage: Ensure workflow according to the mechanisms for implementing the methodology of Six Sigma,\\\\ set controls to ensure that no performance degradation after improved, creating a permanent mechanism to monitor the errors that may show the process and corrected in a timely manner, improve the results of the post-implementation in light of the standards set previously.\\\\ The study also found that there are no significant differences among the scores average of the study sample according to the variables: (Current Position — Degree - the number of years of experience) about the requirements for stages following to apply the methodology of Six Sigma: (definition - Measurement - Analysis - Improvement -Control).
816265
Keywords: سيجما ستة -- تحسين الأداء -- التعليم العالى -- جامعة الدمام